MAPPING OF AREAS OF FOREST AND LAND FIRE VULNERABILITY IN THE SANIANG BAKAR AREA, X KOTO DISTRICT, SOLOK DISTRICT - rezki, sri; Edial, Helfia; Iswandi, Iswandi; Triyatno, Triyatno (International Remote Sensing Applied Journal, 2024)
This research uses quantitative descriptive analysis which has the title "Mapping Areas of Forest and Land Fire Vulnerability in the Saniang Bakar Area, X Koto District, Solok Regency." This research aims to determine the distribution of forest and land fire vulnerability based on the influence of each parameter: land cover, Rain intensity, soil type, height in the Saniang Baka area, research results based on each parameter of land cover which is quite large, fires are dominated by forests covering an area of ​​4946.5 ha and shrubs covering an area of ​​3810.2 ha, the rain intensity parameter is dominated by the very low category. around 200 mm/year, the majority of soil type parameters are Andisols, the height parameters are generally dominated by the sloping category. Understanding the distribution of land surface temperatures using the Land Surface Temperature (LST) algorithm in the Saniang Baka area shows a minimum temperature value of 14.8OC, a maximum temperature of 45.6OC and an average temperature of 30.6OC. The results of the analysis used in the Saniang Bakar area have a general level of vulnerability to forest and land fires in the high category with an area of ​​around 2358.64 Ha.